The Social Gender Construction and Its Influence on Child Custody Determination in Religious Courts in Indonesia - Anisa, Lina Nur (Mukaddimah: Jurnal Studi Islam, 2025)
This article discusses the academic problem of the dominance of social gender construction in determining child custody in Indonesia’s Religious Courts, which hinders substantive justice, especially for women and children. This research employs a library research method with a qualitative approach and socio-legal studies to analyze key literature, regulations, court decisions, and recent empirical studies. The analysis finds that legal argumentation and judges’ narratives often reproduce gender bias through interpretations of the Compilation of Islamic Law and patriarchal social doctrines, resulting in child custody decisions that are frequently not based on the principle of the best interests of the child. The main recommendations are the reformulation of gender-responsive interpretations and regulations of Islamic family law, increased gender literacy among legal practitioners, and cross-sectoral advocacy to create a more just and inclusive family law system. These findings highlight the urgency of reforming Islamic family law based on substantive justice and child protection and provide both conceptual and practical contributions to the development of progressive Islamic studies in Indonesia.